Accessibility in Motion - Developing context-specific accessibility recommendations and re-designing the Thule mobile application - Akin, Enes; Blom, Benjamin (My University, 2026)
Mobile applications are increasingly used in dynamic environments, yet existing accessibility frameworks, such as WCAG 2.2, primarily address static use cases. This Master’s thesis investigates the limitations of current guidelines when faced with Situationally Induced Impairments and Disabilities (SIIDs), including screen glare and reduced dexterity from physical multitasking. In collaboration with Thule Sweden AB, the study employs a Research through Design methodology within a Double Diamond framework. By combining contextual inquiry, general and targeted surveys, and heuristic evaluations, the research identifies critical pain points in active mobile usage. The project culminates in the formulation of 14 context-specific accessibility recommendations and the iterative development of a high-fidelity mobile prototype. This proposed final design features an "Active Mode", an interface variation that re moves non-essential visuals to prioritize cognitive clarity. The findings demonstrate that digital accessibility in high-motion environments relies heavily on functional minimalism, ergonomic adaptability, and error tolerance, ensuring usability supersedes traditional aesthetics.
Keywords: Interaction design, UI design, UX design, user-centered design, design process, prototyping, Accessibility, SIIDs, WCAG